1998
DOI: 10.1007/s11746-998-0201-x
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene alcohols and fatty acids in lipids and nonsaponifiable matter of Lapsana communis L. subspecies communis (Asteraceae)

Abstract: The oil content of samples of aerial parts of Lampsana communis L. subsp. communis, harvested in Indre et Loire (France) at different periods, varies from 1.1 to 2.1%. Nonsaponifiable matter in these samples represents 36.0 to 65.7% of the oil. Yields of triterpene alcohols of nonsaponifiable matter (25.9 to 81.8%) were determined by preparative thin-layer chromatography after saponification. Seven of them were identified by gas chromatography-mass spectrometry (GC-MS). Six of the fatty acids in the aerial par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In France, Fontanel et al (1998a) isolated caffeic, chlorogenic, 3,5-O-dicaffeoylquinic, caftaric and chicoric acid (the major phenylpropanoic constituent in the species) from aerial parts of the plant, as well as the flavonoids, isoquercitrin, luteolin and luteolin-7-O-b-glucuronide. Although the high oil content detected in the Tennessee study was not confirmed by Fontanel et al (1998b), they extracted 2.01% oil, consisting of 43.2% nonsaponifiable matter, a 42.5% mix of nonsaponifiable matter and triterpene alcohols, and 18.4% triterpene alcohols; fatty acids consisting of myristic, palmitic, 10, 13-or 11, 14octadecadienoic, a-linolenic, stearic and arachidic acids; and triterpene alcohols consisting of three unidentified compounds and of taraxerol, b-amyrin, germanicol, aamyrin, lupeol, cycloartenol and c-taraxasterol. Five guaianolide glycosides were identified in extracts of the latex from young stems of L. communis: two previously known sesquiterpene lactone glycosides, crepiside E and tectoroside, and three new compounds, lapsanoside A, B, and C (Fontanel et al1999).…”
Section: Growth and Developmentmentioning
confidence: 79%
See 1 more Smart Citation
“…In France, Fontanel et al (1998a) isolated caffeic, chlorogenic, 3,5-O-dicaffeoylquinic, caftaric and chicoric acid (the major phenylpropanoic constituent in the species) from aerial parts of the plant, as well as the flavonoids, isoquercitrin, luteolin and luteolin-7-O-b-glucuronide. Although the high oil content detected in the Tennessee study was not confirmed by Fontanel et al (1998b), they extracted 2.01% oil, consisting of 43.2% nonsaponifiable matter, a 42.5% mix of nonsaponifiable matter and triterpene alcohols, and 18.4% triterpene alcohols; fatty acids consisting of myristic, palmitic, 10, 13-or 11, 14octadecadienoic, a-linolenic, stearic and arachidic acids; and triterpene alcohols consisting of three unidentified compounds and of taraxerol, b-amyrin, germanicol, aamyrin, lupeol, cycloartenol and c-taraxasterol. Five guaianolide glycosides were identified in extracts of the latex from young stems of L. communis: two previously known sesquiterpene lactone glycosides, crepiside E and tectoroside, and three new compounds, lapsanoside A, B, and C (Fontanel et al1999).…”
Section: Growth and Developmentmentioning
confidence: 79%
“…Such references to culinary uses may belong primarily to the past (Polunin 1969; Plants for a Future 2010), although the species is among wild Asteraceae believed to have potential as a vegetable in Romania (Munteanu and Sirbu 2008). Fontanel et al (1998b) suggested that the large quantity of triterpene alcohols in L. communis could explain its healing properties. The volatile oil has inflammatory and antiseptic properties with potential for exploitation in the treatment of dermatological diseases (Stanciu et al 2007; see also Section 7c).…”
Section: Economic Importance and Environmentalmentioning
confidence: 99%
“…communis contains phenolic acids: caffeic, chlorogenic, caftaric and chicoric, flavonoids, isoquercitrin, luteolin and luteolin-7-O-b-glucuronide (Fontanel et al, 1998a). Its fatty acids consist of myristic, palmitic, 10, 13-or 11, 14-octadecadienoic, a-linolenic, stearic and arachidic acids (Fontanel et al, 1998b). The triterpene alcohol with taraxerol, b-amyrin, germanicol, aamyrin, lupeol, cycloartenol and ctaraxasterol were also extracted from nipplewort (Fontanel et al, 1999).…”
Section: Introductionmentioning
confidence: 99%